-5(7x-1)+6(x-5)=62

Simple and best practice solution for -5(7x-1)+6(x-5)=62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(7x-1)+6(x-5)=62 equation:


-5(7x-1)+6(x-5)=62

We simplify the equation to the form, which is simple to understand
-5(7x-1)+6(x-5)=62

Reorder the terms in parentheses
+(-35x+5)+6*(x-5)=62

Remove unnecessary parentheses
-35x+5+6+*(+x-5+)=+62

Reorder the terms in parentheses
-35x+5+(+6x-30)=62

Remove unnecessary parentheses
-35x+5+6x-30=+62

We move all terms containing x to the left and all other terms to the right.
-35x+6x=+62-5+30

We simplify left and right side of the equation.
-29x=+87

We divide both sides of the equation by -29 to get x.
x=-3

See similar equations:

| (5+v)(4v+1)=0 | | 7(-8x-1)-8(2+x)=41 | | 7t-9=24+4t | | 4s-8=1+s | | -5x-9x=-112 | | 6x+8x=84 | | -66=6+6x | | -13=7(2x-1)+5 | | 7x+8=10x+17 | | 6(w+4)=3w+6 | | 2(x-5)+7= | | 11x+6(3-x)=3 | | 2(x-7)+7= | | 12=-3600+3600 | | 4-5(x+1)=7 | | 7(v-5)=7 | | w-4=-10 | | x^2+y^2+4x-y-2=0 | | 3+5x(6-4+1)= | | 12x^3y^2-24x^2y^3+16x^2y^4=0 | | -4=-3(4+5x)-4(-2+6x) | | 4+3x=17-6x | | 5-3x=15+0.5x | | 10x-24=2x+8 | | 9-5x=5-3x | | 7x+4=2x+2 | | (9)(7)-(5)(-2)= | | 3-2n=11 | | 7-(-1-4)= | | 8+3x=18+4x | | -2-4+7+3(-4)+17= | | 4-9x=26+2x |

Equations solver categories